SISTEM REMUNERASI DOSEN BADAN LAYANAN UMUM PERGURUAN TINGGI - Novi Trisnawati; Helmy Adam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aimed to evaluate lecturer remuneration system in University’s Public Service Agency.This research used qualitative descriptive method with researcher as the key instrument. The data of the research were obtained through the collection of documents. Theresult of the research show that the remuneration system of Public Service Agency must meets the principle of fair, equitable , reasonable, proportionality, equality and appropriateness in accordance with PP Nomor 23 Tahun 2005 and PMK Nomor 10 Tahun 2006. However, the remuneration system lecturer at the University has met the principle of transparent and single salary in accordance with the law. Researchers recommend models of remuneration in accordance with the laws and regulations and it is suitable for use in oraganitation Public Service Agency of University. Keywords: remuneration, lecturer, Public Service Agency, university